Food Sufficiency, Tariffication Policy, and Business Strategy: A New Business Model for the Rice Milling Industry in the Philippines - Sarah Calma Alvarez; Feliciana Jacoba; Olive Chester Cuya Antonio; Arneil Garcia Gabriel; Macky Ciriaco Herezo (MEC-J (Management and Economics Journal), 2022)
Rice is a primary commodity in the Philippines and a staple food for Filipino families. Climate change, low yield, and decreasing number of Filipinos engaged in agriculture lead to the instability in the supply of rice and fluctuation in market price affecting local farmers, rice millers, and consumers. In an attempt to address rice shortage and lower retail prices, Republic Act No. 11203 or Rice Tariffication Law was promulgated. Given the contribution of Nueva Ecija province in the rice economy of the country, it is vital to analyze the impact of the policy in the province, specifically, on the operations of 82 registered rice millers using descriptive method of research. Results indicate that the rice millers observe the traditional practices in trading milled rice. Most of them are not engaged in importation and are facing challenges related to the sudden policy reform. From the findings of the study, a new business model is recommended to help rice millers increase the scope of their operations and acquire necessary funding from banking institutions. The new model is seen to help the rice millers gain income from different ventures, allowing them to expand, grow and help the economy in the long run. Thus, raising sustainable investments in the rice industry in the province and in the Philippines.